2016
DOI: 10.1055/s-0036-1594306
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sexual Dysfunction among Expectant Women

Abstract: To identify pregnancy as a causative factor of sexual dysfunction among expectant women. A prospective study with 225 expectant mothers seen in the prenatal clinic of a federal university. Sexual function was evaluated by means of the Female Sexual Function Index (FSFI), and all domains were analyzed (desire, arousal, lubrication, orgasm, satisfaction, and pain). Initially, a univariate analysis of the sample was done. The averages for each domain according to the risk of sexual dysfunction (FSFI ≤ 26.5) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 21 publications
0
16
0
3
Order By: Relevance
“…This descriptive-analytical study was conducted in 2019 on women with gestational diabetes for whom diabetes was diagnosed based on gestational diabetes screening in week 24-28 of pregnancy by the two-hour oral glucose tolerance test (OGTT), which involved taking 75 g of glucose (20), in the past month. These women, who visited the clinics affiliated with Mazandaran University of Medical Sciences, lived with their husbands; were literate; sexual activity during pregnancy was not prohibited for them (due to spotting, risk of miscarriage, etc.…”
Section: Methodsmentioning
confidence: 99%
“…This descriptive-analytical study was conducted in 2019 on women with gestational diabetes for whom diabetes was diagnosed based on gestational diabetes screening in week 24-28 of pregnancy by the two-hour oral glucose tolerance test (OGTT), which involved taking 75 g of glucose (20), in the past month. These women, who visited the clinics affiliated with Mazandaran University of Medical Sciences, lived with their husbands; were literate; sexual activity during pregnancy was not prohibited for them (due to spotting, risk of miscarriage, etc.…”
Section: Methodsmentioning
confidence: 99%
“…A literatura tem mostrado diferentes abordagens de estudo em relação à temática. Ainda podem-se encontrar estudos que limitam a sexualidade a simples funcionalidade da vida sexual, não contemplando aspectos subjetivos, afetivos e emocionais atrelados à composição de toda trajetória sexual do indivíduo (Monteiro et al, 2016).…”
Section: Sexualidade E Satisfação Sexualunclassified
“…In Brazil, Monteiro et al [11] reported a prevalence of sexual dysfunction of 66.7% among expectant women. Meanwhile, a Japanese study [12] reported a prevalence of 62.2% in pregnant women, and lower mean FSFI values for women who delivered via Caesarean section.…”
Section: Introductionmentioning
confidence: 99%